Augmentative and alternative communication (AAC) training provision for professionals in England. Issue 3 (18th September 2017) - Wallis, Samantha; Bloch, Steven; Clarke, Michael
Abstract : Purpose: The purpose of this paper is to document augmentative and alternative communication (AAC) training provision by clinical services in England. Design/methodology/approach: A questionnaire was used to obtain the following information concerning AAC training provision; frequency, length, type, content and cost, trainee occupations and numbers, and future training priorities, and information concerning training providers – service type, geographical area. Findings: In total, 98 clinical service training providers in England responded. Services commonly reported providing AAC training to speech and language therapists, teaching assistants and teachers. Training around "use of specific AAC products, systems and technology" and "introducing/awareness raising of AAC products" were rated as high priority for future training and were two of the three subject areas where services reported the highest percentage of training. Training was predominantly provided at a foundation (basic) level. Originality/value: There is no consensus on the amount or content of AAC training which professionals in England must receive. Evidence suggests that AAC training for pre-qualification professionals is limited and this paper has identified variation in the amount and type of post-qualification AAC training. While knowledge concerning specific AAC systems is necessary, focussing training primarily on this area may not address critical gaps in knowledge. There is a need for specific recommendations regarding AAC training for professionals in this field, to ensure professionals can fully support people who use AAC.